Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Overlooked effects of common alcohol quenching agents on electron transfer pathway in persulfate activation system - Xuerong Zhou; Lin Zhang; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Qihong Yang; Bing Ding; Cui Lai; Ming Yan; Zizhu Peng (Chemical Engineering Journal, 2026)

Viper-inspired vigilance: A biomimetic PPy@M(OH)(OCH3) (M = Co, Ni) smart armor endows cotton with high-efficient fire-resistance, graded fire-alarming, and identification for firefighting postures - Caiyu Rong; Xiang Dong; Shidai Zhang; Shuqin Ding; Zhaoxin Zhang; Yan Ma; Zixin Lin; Yuhe Song; Jiayi Zhang; Shibin Nie; Konghu Tian (Chemical Engineering Journal, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Self-cleaning van der Waals lamination for two-dimensional electronics - Chang Liu; Shuimei Ding; Xudong Wang; Guichen Teng; Jinhua Zeng; Ying Zhang; Qianru Zhao; Huiting Wang; Binmin Wu; Shuaiqin Wu; Yan Chen; Tie Lin; et al. (Science Bulletin, 2026)

Manipulating phloem iron transport using the phloem-specific promoter OsSUT1 enhances grain iron accumulation in rice - Yan Lin; Yan Zhu; Haohao Hu; Bingjie Liu; Yuxiang Hu; Yanfeng Ding; Lin Chen (Plant Science, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Oxygen vacancy engineering in Ni-CeO2 catalysts for efficient and coke-resistant dry reforming of methane - Shimin Yan; Wuji Lai; Yue Ding; Wenju Jiang; Zhongde Dai; Lin Yang; Junfeng Zheng; Lu Yao (Fuel, 2026)

Revealing the kinetic promotion mechanism of carbon nanotubes to methane hydrate formation: As to the situation coupled with traditional kinetic promoter L-leucine - Yan Lin; Yan-Ling Guo; Zhi-Yuan Wang; Jie Zhong; Xiao-Ming Wang; Yi-Ning Ding; Hong-Zheng Lu; Fei Wang; Xiao-Lin Wang (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Analysis of nitrogen distribution in chemical looping gasification of kitchen waste and soy protein as a model compound with CuFe2O4 and NiFe2O4 oxygen carriers - Shiwen Fang; Luzhou Ding; Yan Lin; Shuchang Yan; Xiongwei Zheng; Zhen Huang; Hongyu Huang (Fuel, 2026)

Towards integrated pollution control in inland watersheds: addressing multiple challenges through watershed-scale technological systems and targeted control strategies - Mei-Yun Lu; Jie Ding; Xin-Lei Yu; Zi-Tong Zhao; Yi-Lin Zhao; Ji-Wei Pang; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Environmental Pollution, 2026)

In situ-based spectral characteristics of first-year landfast ice in eastern Liaodong Bay, Bohai sea - Qingkang Hou; Yu Yan; Zhikun Lin; Chenchen Yao; Jiayu Ding; Jinghan Xu; Chenyu Shu; Lei Ren; Yingjun Xu (International Journal of Remote Sensing, 2026)

In situ spectral analysis of sea ice contaminated with multiple substances in Liaodong Bay, Bohai Sea - Jinghan Xu; Yu Yan; Zhikun Lin; Qingkang Hou; Jiayu Ding; Chenchen Yao; Lei Ren; Chenyu Shu; Yingjun Xu (Marine Pollution Bulletin, 2026)

Corrigendum to “Virus-induced redox cycling in Fe(II)/peracetic acid systems: dual roles as reactant and catalytic promoter” [Water Research 289 (2026) 124920] - Xiao Liu; An Ding; Wei Lin; Wei Qiu; Geoffroy Lesage; Marc Heran; Yan Zhao; Chuyang Y. Tang (Water Research, 2026)

Identification of the chili powder with illegal additive Sudan I by shifted-excitation Raman difference spectroscopy system - Shu-Wei Hu; Jun-Qin Xu; Yan-Chi Chao; Jhen-Yue Chang; Ding-Zheng Lin (Food Chemistry, 2026)

Gut microbiota-tryptophan-serotonin axis drives anxiety-like behavior via NLRP3-mediated neuronal pyroptosis in the medial prefrontal cortex - Guiqiang Zhou; Xing Wang; Tongzhou Qin; Ling Guo; Jiajin Lin; Zhaowen Zhang; Peng Gao; Yan Zhou; Wei He; Jing Li; Guirong Ding (Apoptosis, 2026)

Environmental factors shape the intestinal microbiota and function of Manila clam Ruditapes philippinarum - Bifu Gan; Guiling Li; Yanru Xu; Jingmiao Yang; Weilang Lin; Xiaobo Yan; Maozi Lin; Guangmao Ding; Fang Su; Qizhen Xiao (Frontiers in Marine Science, 2026)
Intestinal microbiota of aquatic animals is closely associated with the environment, influencing their health, immune defense, and environmental adaptability. To understand the relationships among the Manila clam ( Ruditapes philippinarum ) intestinal microbiota, the bacterial communities in their habitats, and environmental factors, as well as the characteristics and potential functions of the intestinal microbiota. This study systematically analyzed the bacterial communities in the clam intestines, seawater, and sediment samples from two typical habitats using 16S rRNA gene (V3-V4) sequencing. The results revealed significant differences in bacterial community composition among the intestines, seawater and sediment, with pronounced regional variations also evident within the same sample type. The clams gut microbiota in Fuqing was predominantly composed of Alphaproteobacteria , Gammaproteobacteria , Bacteroidota , Bacillota , and Cyanobacteria . In Putian, Cyanobacteria comprised an exceptionally high proportion. However, Bacillota , Bacteroidota , and Actinomycetota showed similar relative abundances in both regions, indicating a potential “core bacterial community”. Regarding the α-diversity of gut microbiota, although no significant differences were observed between clam samples from the two regions, their diversity was significantly lower than that of the sediment bacterial communities. The intestinal bacterial communities exhibited high similarity to the aquatic bacterial communities in terms of richness, diversity, and dominant species abundance, and it shares most of the ASVs with the sediment, suggesting that environmental microorganisms may serve as the primary source of the clam intestinal microbiota. Environmental drivers of bacterial communities differed regionally. In Fuqing, bacterial communities were associated with temperature, DO, pH, and salinity, and exhibited broader niche widths; in Putian, they were mainly influenced by nutrients, showing narrower niches. Compared to bacterial networks in the environment, the interactions among members within the gut bacterial communities of clams display modularity, indicative of functional specialization. The composition and functions of the intestinal microbiota of clams vary significantly in different environments, which may be a manifestation of their ecological adaptability. The composition and function of clam intestinal microbiota varied with environment, reflecting their ecological adaptability. These findings provide a scientific theoretical basis for water quality regulation and disease prevention in aquatic animal farming operations.

Molecular and optical signatures of labile dissolved organic matter during bloom senescence in the Amundsen Sea Polynya - Hui Lin; Qiang Hao; Wei Zhang; Zhenwei Yan; Hao Zhang; Ziming Fang; Yuan Gao; Yong Yu; Ding He (Limnology and Oceanography, 2026)
The Amundsen Sea Polynya (ASP) in the Southern Ocean serves as a potentially significant carbon sink, where phytoplankton blooms drive intense primary production and dissolved organic matter (DOM) cycling. This study focuses on DOM dynamics during the late‐summer bloom phase dominated by Phaeocystis antarctica . Despite the ASP's high productivity, DOM characteristics and their response to bloom senescence remain poorly resolved, limiting insights into carbon sequestration efficiency. We integrated absorbance and fluorescence spectroscopy with Fourier transform ion cyclotron resonance mass spectrometry to analyze seawater samples collected along transects in the ASP during austral summer 2022. Key findings include non‐exponential chromophoric DOM spectra with distinct shoulders at 270–290 nm (aromatic amino acids) and 300–350 nm (mycosporine‐like amino acids), elevated protein‐like fluorescent DOM components linked to P. antarctica degradation, and enrichment of labile, low‐molecular‐weight compounds ( −1 ) amid reduced chlorophyll a (3.81 ± 0.77 mg·m −3 ), indicating DOM release under iron‐replete, nitrate‐limited conditions. This work advances knowledge by identifying unique phytoplankton‐derived DOM signatures that challenge conventional optical metrics like spectral slopes in polar systems, highlighting autochthonous production over terrestrial inputs. Broader implications include improved predictions of carbon cycling in expanding polynyas under climate change, emphasizing reduced sequestration due to labile DOM remineralization and its vulnerability to warming‐induced shifts in Antarctic ecosystems.

Electroplating parks as hidden sources of novel plastic additives: Occurrence, migration pathways, and ecological risks - Zi-Tong Li; Zecong Ding; Yingjie Chen; Kai Cui; Li Wang; Hai-Yan Zhang; Qian Jiang; Li-Qian Lin; Jian-Liang Zhao (Water Research, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Two-stage tandem co-fermentation of food waste and waste activated sludge assisted by endogenous alkaline hydrolase for short chain fatty acids-oriented biorefinery - Yan Wang; Peixiang Zhang; Jinxuan Liu; Qiao Wei; Jiangbo Ding; Xinyi Li; Jinsuo Lu; Lin Xu; Wenkai Li; Heliang Pang (Journal of Cleaner Production, 2026)

Tilapia skin collagen peptides‑calcium chelates:Structural characterization, stability, in vitro and in vivo anti-osteoporosis mechanism - Xing Xie; Meng-ting Zhang; Chun-lin Huang; Jin-yu Wang; Qiao Ding; Yan-xia Xiong; Zong-cai Tu; Lu Zhang (Food Research International, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Virus-induced redox cycling in Fe(II)/peracetic acid systems: dual roles as reactant and catalytic promoter - Xiao Liu; An Ding; Wei Lin; Wei Qiu; Geoffroy Lesage; Marc Heran; Yan Zhao; Chuyang Y. Tang (Water Research, 2026)

Sugar-gibberellin crosstalk mediates leaf elongation in rice (Oryza sativa L.) - Jiaqi Bai; Bingjie Liu; Weiyan Zhang; Yan Zhu; Ganghua Li; Zhenghui Liu; Yanfeng Ding; Lin Chen (Plant Science, 2026)

Eight previously undescribed flavonoids and four previously undescribed bibenzyls from Macaranga kurzii and their potential antiviral activities - Yan-Zi Ma; Ding-Cheng Zhang; Liu Yang; Xue-Wen Wu; Bo Li; Muhammad Aurang Zeb; Yuan-Lin Kong; Xue-Mei Zhou; Wei-Lie Xiao; Chang-Bo Zheng; Xiao-Li Li (Phytochemistry, 2026)

Human umbilical cord MSC-derived exosomes attenuate radiation-induced pulmonary fibrosis via remodeling the gut-lung axis in mice - Yan Zhou; Haonan Wang; Ling Guo; Xiaodie Liu; Xing Wang; Yue Liu; Mengjuan Shang; Bo Zheng; Kewei Li; Lin Liu; Jing Li; Guirong Ding (Life Sciences in Space Research, 2026)

Dynamic Ni0-Niδ+ cycling promotes the activity and stability of a NixMgyO catalyst for CO2/CH4 reforming - Wuji Lai; Shimin Yan; Jiahao Lu; Yue Ding; Li Li; Wenju Jiang; Zhongde Dai; Lin Yang; Junfeng Zheng; Shenggui Ma; Changwei Hu; Lu Yao (Chemical Engineering Journal, 2026)

The balance application of nano-macronutrients promote growth, productivity and quality through modulation of antioxidative activities in wheat - Mingliang Ding; Lijun Tang; Lin Zhang; Yan Yang; Hongsheng Li; Qi Ma; Shaoxiang Li; Jia Liu; Cuiping Zhang; Kun Liu; Shah Fahad; Sidra Fatima; et al. (Plant Science, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

The influence of different physical pretreatments on the enzymatic hydrolysis effect and flavor characteristics of high-temperature soybean meal - Xue Qin Zhu; Shi Lin Zhang; Jia Wen Duan; Yan Ding; Tie Hua Zhang; Zhou Yong Dong (Food Chemistry, 2025)

Integrating hydrogen-bonding nanotrap into a cage-like MOF for natural gas upgrade and MTO product separation - Wen-Jie Shi; Meng-Wei Chen; Yong-Zhi Li; Hai-Yan Chen; Yichao Lin; Hetang Wang; Lei Hou; Gang-Ding Wang (Chemical Engineering Journal, 2025)

Chemical constituents from the branches of Broussonetia papyrifera and their chemotaxonomic significance - Cong-Xi Gao; Wen-Jie Ma; Wu-Yan Chen; Hong-Ji Shi; Ding Tian; Jian-Lin Hu; Kou Wang (Biochemical Systematics and Ecology, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Transcription factor E93 regulates vitellogenesis via the vitelline membrane protein 26Ab gene in Chilo Suppressalis - Siyang Chen; Yingjuan Sun; Suijie Kuang; Yan Tang; Wenbing Ding; Hualiang He; Jin Xue; Qiao Gao; Hongshuai Gao; Youzhi Li; Lin Qiu (Molecular Biology Reports, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Engineering scaffold-cell interactions for cultured meat: mechanisms, materials, and emerging AI-driven strategies - Linzi Li; Yijun Zhang; Zipeng Xu; Shuai Yan; Nuo Yan; Cong Zhao; Yabin Niu; Shijie Ding; Guanghong Zhou; Lin Chen; Xianchao Feng (Trends in Food Science & Technology, 2025)

Sleep quality is enhanced by egg yolk hydrolysate through modulation of GABAergic and serotonergic neurotransmission in mice - Yifang Yan; Mahmoud Abou-Elsoud; Wei Liu; Lixian Ding; Lin Zhang; Yi Wang; Meiyu Liu; Xi Huang (Food Bioscience, 2025)

Characterization of CD8+ T Cells in large yellow croaker Larimichthys crocea and their dynamics in response to Cryptocaryon irritans infection - Guolong lai; Xinran Li; Sichang Liu; Luyang Zhao; Mengtian Xie; Li Huang; Wenxuan Zhang; Wenbing Bao; Yan Lin; Xinhua Chen; Yang Ding (Fish & Shellfish Immunology, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Phenotypic and functional characterization of CD4-2+ T cells in large yellow croaker Larimichthys crocea - Xinran Li; Guolong Lai; Yan Lin; Sichang Liu; Wenbing Bao; Wenxuan Zhang; Li Huang; Guangming Shao; Shihao Chen; Yang Ding; Xinhua Chen (Fish & Shellfish Immunology, 2025)

Recyclable, photothermal dual responsive shape memory epoxy vitrimers containing dynamic oxime-carbamate bonds, dynamic ester bonds and hydrogen bonds based on vegetable oil - Xiaoqi Xie; Shouhai Li; Mei Li; Haiyang Ding; Mingtao Lin; Lina Xu; Na Yao; Qingyuan Feng; Xiaohua Yang; Xiao Feng; Yan Zhang; Yi Xing (Chemical Engineering Journal, 2025)

Soil respiration and carbon sequestration response to short-term fertilization in wheat-maize cropping system in the North China Plain - Jian Zhang; Peikun Li; Lin Li; Mina Zhao; Peisen Yan; Yuan Liu; Wei Li; Shengyan Ding; Qinghe Zhao (Soil and Tillage Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

River inflow and seawater intrusion shape distinct phytoplankton communities in jinghai bay, a coastal bay of the Yellow Sea - Jinchang Sui; Dongsheng Ding; Yan Zhang; Lin Zhu; Zhengguo Cui; Jun Sun; Yuqiu Wei (Marine Environmental Research, 2025)

Identification of heavy metal transport-related genes and microRNAs in response to cadmium toxicity and micronutrient deficiency in barley roots - Liuhui Kuang; Jian Chen; Jie Ding; Tao Yan; Fei Gao; Lin Li; Zhigang Han; Dezhi Wu (Journal of Hazardous Materials, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Recent decline of sea ice area in the Bohai Sea over the period 2001 to 2023 - Zhikun Lin; Yu Yan; Yingjun Xu; Qingkang Hou; Jialin Zhang; Jiayu Ding (Journal of Marine Systems, 2025)

Ionotropic receptors participate in the perception of sinigrin in Plutella xylostella adults - Zhi-Qiang Wei; Ya-Xin Wang; Ji-Xiang Wang; Xuan-Pu Luan; Chen Ding; Fan-Zheng Meng; Yu He; Qi Yan; Jin Zhang; Shuang-Lin Dong (Insect Biochemistry and Molecular Biology, 2025)

Melatonin Ameliorates Senescence of Mouse Auditory Cell Line HEI-OC1 Cells by Suppressing NLRP3 Inflammasome-Mediated Pyroptosis - Yongqing Ding; Yachao Liu; Dong Li; Ruili Hu; Zedong Tian; Lihang Yang; Yanping Li; Yantao Lin; Yan Qu (Molecular Neurobiology, 2025)

High-resolution estimation of urban anthropogenic carbon emissions - Zirong Lin; Bo Huang; Jia He; Yizhen Yan; Man Xiao; Qinrui Luo; Zhulin Qi; Xiaotian Ding (Sustainable Cities and Society, 2025)

Chemical structures, antioxidant capacities, and immunostimulatory activities of pectic polysaccharides from jujube fruits collected from different producing areas - Jing Feng; Xiao Luo; Bo Li; Xiao-Yan Yang; Lin Zhang; Jing-Wei Huang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Food Bioscience, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Exploring the comprehensive factors influencing tacrolimus pharmacokinetics in early renal transplant recipients: A population pharmacokinetic analysis - Yan Zhang; Ling Xue; Linkun Hu; Liangliang Wang; Hao Pan; Yuxin Lin; Xiaoliang Ding; Yuhua Huang; Liyan Miao (European Journal of Clinical Pharmacology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Identification of Dendrobium officinale species and authentication of commercial products by DNA barcoding and high-resolution melting analysis - Zhilong He; Zhao Yang; Cui Dong; Shanshan Yan; Jing Lin; Hexigeduleng Bao; Fan Tang; Leilei Zhang; Cheng Zhu; Yan Hu; Yanfei Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Harnessing multi-target nanosweepers inhibiting β-amyloid aggregation, scavenging reactive oxygen species and overcoming the blood brain barrier for rescuing Alzheimer’s disease - Yixuan Wang; Chaoren Yan; Yuming Qi; Ruobing Zhao; Yan Wan; Zhaoyuan Lyu; Yansong Li; Zhijuan Wang; Changqing Li; Yuehe Lin; Qian Chen; Shichao Ding; et al. (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Untargeted metabolomics reveals the formation pathways of bound sulfite in sodium metabisulfite-soaked Hemerocallis citrina Baroni - Jianing Li; Zheng Zhou; Qi Wu; Zhaofang Liu; Lin Zhu; Shuhong Ye; Yan Ding (Food Chemistry, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Anterior and posterior cerebral white matter show different patterns of microstructural alterations in young adult smokers - Lei Jiang; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Yan Zhou; Fuchun Lin (Brain Imaging and Behavior, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Comprehensive Analysis of the SUMO-related Signature: Implication for Diagnosis, Prognosis, and Immune Therapeutic Approaches in Cervical Cancer - Xing Zhang; Jian Cao; Xiuting Li; Yan Zhang; Wenjing Yan; Bo Ding; Jing Hu; Haohan Liu; Xue Chen; Yamei Nie; Fengying Liu; Ning Lin; et al. (Biochemical Genetics, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

An Intelligent Indicator Film Based on Food Derived Materials for Real-Time Visual Monitoring of Salmon Freshness - Zhiyu Yan; Siqi Zhang; Songyi Lin; Ni Ding; Jiaxin Qiang; Tongtong Xie; Simin Zhang (Journal of Aquatic Food Product Technology, 2024)

Deep mineralization of bisphenol A via Cu–Mn spinel oxide nanospheres anchored N-doped carbon activated peroxymonosulfate - Xiaobo Wang; Lin He; Yu Zhou; Nan Wang; Lihua Zhu; JunTao Yan; Deng Ding; Wenjun Zhu; Xiaohua Zuo; Jinpeng Wang; Xiaoyong Wu (Chemical Engineering Journal, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Reduction of haemoglobin is related to metal mixtures exposure in Chinese preschoolers: Joint effect models - Ye Fu; Minghui He; Yang Liu; Mingzhu Li; Meiqin Zhu; Yan Wang; Wei Lin; Lili Yu; Liting Yang; Yao Zhang; Yanli Liu; Hongxian Ji; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Narrow bandgap Sn-Pb perovskite solar cells with high operational stability modulated by imidazoline derivative - Feilin Zou; Chenghao Duan; Zhuojia Lin; Zheng Zhang; Shuang Xu; Chang Chen; Jianwei Chen; Jiong Li; Shibing Zou; Liming Ding; Hongze Luo; Keyou Yan (Chemical Engineering Journal, 2024)

Discrimination of untreated and sodium sulphite treated bean sprouts by Fourier transform infrared spectroscopy and chemometrics - Yaxin Li; Baoguo Chen; Shuhong Ye; Qi Wu; Lin Zhu; Yan Ding (Food Additives & Contaminants: Part A, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Synthetic consortia of four strains promote Schisandra chinensis growth by regulating soil microbial community and improving soil fertility - Yan Li; Zanbo Ding; Tengqi Xu; Yulong Wang; Qiaolu Wu; Tianjiao Song; Xiaomin Wei; Juane Dong; Yanbing Lin (Planta, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

Multi-functional hydrogen- and oxygen-capturing FeCo-N-C catalyst with improved hydrogenation of nitroarenes and ORR activity - Hsiu-Chung Tu; Yu-Lin Hsiao; Yi-Dong Lin; Yan-Gu Lin; Ding-Liang Liao; Ko-Shan Ho (Chemical Engineering Journal, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Inhibition of Sucrose Source-to-Sink Transport Reduces Iron Accumulation in Rice - Yan Lin; Yuxiang Hu; Yue Wu; Yue Qiu; Yanfeng Ding; Lin Chen (Journal of Plant Growth Regulation, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Application of iron tailings in the coagulation of landfill leachate by bipolar membrane electrodialysis - Yanchao Jin; Guodong Wang; Zheng Li; Chun-Yan Lin; Li-Ping Li; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Journal of Cleaner Production, 2024)

Self-powered Fenton-like process for propranolol degradation and bacterial inactivation with Mg-CuO/CeO2/BC composites - Yanchao Jin; Xiongjian Chen; Peiwen Huang; Chun-Yan Lin; Rui Ding; Riyao Chen (Journal of Environmental Chemical Engineering, 2024)

Influence of speed measurement method on performance of an electric-drive maize precision planter - Lin Ling; Guangwei Wu; Changkai Wen; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Jianhong Ding; Zhijun Meng; Bingxin Yan (Biosystems Engineering, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Study on the catalytic hydrodeoxygenation of lignin dimers: Adsorption properties and linkages cleavage - Bochao Yan; Wenbin Ding; Gaojie Shi; Xiaoyu Lin; Suping Zhang (Bioresource Technology, 2024)

Environmental damages, cumulative exergy demand, and economic assessment of Panus giganteus farming with the application of solar technology - Hanting Cheng; Xiaohui Zhou; Yang Yang; Lin Xu; Ye Ding; Tingliang Yan; Qinfen Li (Science of The Total Environment, 2024)

Bacteria-driven copper redox reaction coupled electron transfer from Cr(VI) to Cr(III): A new and alternate mechanism of Cr(VI) bioreduction - Xiaoye Min; Kejing Zhang; Jianxin Chen; Liyuan Chai; Zhang Lin; Long Zou; Weizao Liu; Chunlian Ding; Yan Shi (Journal of Hazardous Materials, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

3D printing of customizable and lightweight multilayer MXene/nanocellulose architectures for tunable electromagnetic interference shielding via direct ink writing - Lei Chen; Tian Mai; Xing-Xiang Ji; Pei-Lin Wang; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

Stretchable textile with ultra-high electromagnetic interference shielding performance based on porous wrinkled conductive network - Tai-Bao Yang; Ji-You Zong; Hao Lin; Ding-Xiang Yan; Jun Lei; Zhong-Ming Li (Chemical Engineering Journal, 2023)

Synergistic effect between monophosphine species for regioselective hydroformylation of olefin with CO2 - Guoqing Wang; Miao Jiang; Zhao Sun; Leilei Qian; Guangjun Ji; Lei Ma; Cunyao Li; Zhaozhan Wang; Yong Yang; Xiangsong Lin; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2023)

Environmental exposure and ecological risk of perfluorinated substances (PFASs) in the Shaying River Basin, China - Ya-Hui Zhang; Ting-Ting Ding; Zi-Yan Huang; Hong-Yi Liang; Shi-Lin Du; Jin Zhang; Hui-Xian Li (Chemosphere, 2023)

Konjac glucomannan/low-acyl gellan gum edible coating containing thymol microcapsule regulates cell wall polysaccharides disassembly and delays postharvest softening of blueberries - Peng Huang; Jie Ding; Chunyan Liu; Hongying Li; Chenlin Wang; Yezi Lin; Dur E. Sameen; Md Alomgir Hossen; Mingrui Chen; Jing Yan; Yaowen Liu; Wen Qin (Postharvest Biology and Technology, 2023)

Dual Förster resonance energy transfer effects enables high photocurrent density and high fill factor in ternary organic solar cells - Hongqian Wang; Daobin Yang; Pengfei Ding; Lin Xie; Zhenyu Chen; Shuncheng Yang; Pengyu Yan; Yuanyuan Meng; Jianqi Zhang; Zhixiang Wei; Ziyi Ge (Chemical Engineering Journal, 2023)

Molecular networking-guided isolation of undescribed antifungal odoriferous sesquiterpenoids from a marine mesophotic zone sponge-associated Streptomyces sp. NBU3428 - Huimin Wen; Dashuai Zhang; Hang Zhao; Yawen Zhang; Xiaojun Yan; Wenhan Lin; Shan He; Lijian Ding (Phytochemistry, 2023)

Toward ultra-high efficiency tandem OLEDs: Benzothiazole-based bipolar hosts and specific device architectures - Jui-Ming Wang; Ting-Chun Lee; Chia-Chen Chung; Wun-Yu Chen; Sih-Yu Wu; Yan-Ding Lin; Yuan Jay Chang; Chin-Wei Lu; Chih-Hao Chang (Chemical Engineering Journal, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar - Yanchao Jin; Peiwen Huang; Xiongjian Chen; Li-Ping Li; Chun-Yan Lin; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Environmental Pollution, 2023)

Bilayer metal-organic frameworks/MXene/nanocellulose paper with electromagnetic double loss for absorption-dominated electromagnetic interference shielding - Tian Mai; Wen-Yan Guo; Pei-Lin Wang; Lei Chen; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Physiological response and photosynthetic recovery to an extreme drought: Evidence from plants in a dry-hot valley savanna of Southwest China - Da Yang; Yang-Si-Ding Wang; Qin Wang; Yan Ke; Yun-Bing Zhang; Shi-Bao Zhang; Yong-Jiang Zhang; Nate G. McDowell; Jiao-Lin Zhang (Science of The Total Environment, 2023)

Remarkable adsorption capacity of Cu2+-doped ZnAl layered double hydroxides and the calcined materials toward phosphate - Ding Ling Gao; Wei Wei Lin; Qiao Jing Lin; Fei Fei Dai; Yan Xue Xue; Jian Hua Chen; Yu Xiang Liu; Yang Huang; Qian Yang (Journal of Environmental Chemical Engineering, 2023)

Polyketides with antimicrobial activities from Penicillium canescens DJJ-1 - Jia-Peng Wang; Yan Shu; Sheng-Qi Zhang; Lin-Lin Yao; Bing-Xian Li; Li Zhu; Xiao Zhang; Huai Xiao; Le Cai; Zhong-Tao Ding (Phytochemistry, 2023)

Quantification and visualization of meat quality traits in pork using hyperspectral imaging - Xi Tang; Lin Rao; Lei Xie; Min Yan; Zuoquan Chen; Siyi Liu; Liqing Chen; Shijun Xiao; Nengshui Ding; Zhiyan Zhang; Lusheng Huang (Meat Science, 2023)

Bibliometric overview of research progress, challenges, and prospects of rural domestic sewage: Treatment techniques, resource recovery, and ecological risk - Le Zhong; Jie Ding; Tong Wu; Yi-lin Zhao; Ji Wei Pang; Ji-Ping Jiang; Jun-Qiu Jiang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Water Process Engineering, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

RNA interference knockdown of insulin receptor inhibits ovarian development in Chilo suppressalis - Shuang Wu; Yan Tang; Shaojun Su; Wenbing Ding; Hualiang He; Jin Xue; Qiao Gao; Lin Qiu; Youzhi Li (Molecular Biology Reports, 2022)

Reciprocal modulation between cigarette smoking and internet gaming disorder on participation coefficient within functional brain networks - Xianxin Qiu; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Hao Lei; Yan Zhou; Fuchun Lin (Brain Imaging and Behavior, 2022)

Functional characterization of two homologs of yeast acetyl-coenzyme A synthetase in the entomopathogenic fungus Beauveria bassiana - Jia-Hui Lei; Hai-Yan Lin; Jin-Li Ding; Ming-Guang Feng; Sheng-Hua Ying (Archives of Microbiology, 2022)

Systematic contributions of CFEM domain‐containing proteins to iron acquisition are essential for interspecies interaction of the filamentous pathogenic fungus Beauveria bassiana - Yue‐Jin Peng; Jia Hou; Hao Zhang; Jia‐Hui Lei; Hai‐Yan Lin; Jin‐Li Ding; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2022)
Summary Common in fungal extracellular membrane (CFEM) domain is unique in fungal proteins and some of which contribute to iron acquisition in yeast. However, their roles in iron acquisition remain largely unknown in filamentous fungi. In this study, 12 CFEM‐containing proteins were bioinformatically identified in the filamentous entomopathogenic fungus Beauveria bassiana , and the roles of 11 genes were genetically characterized. Transmembrane helices were critical for their association with intracellular membranes, and their number varied among proteins. Eleven CFEM genes significantly contribute to vegetative growth under iron starvation and virulence. Notably, the virulence of most disruptants could be significantly weakened by a decrease in iron availability, in which the virulence of Δ Bbcfem7 and 8 strains was partially recovered by exogenous hemin. Δ Bbcfem7 and 8 mutants displayed defective competitiveness against the sister entomopathogenic fungus Beauveria brongniartii . All 11 disruptants displayed impaired growth in the antagonistic assay with the saprotrophic fungus Aspergillus niger , which could be repressed by exogenous ferric ions. These findings not only reveal the systematic contributions of CFEM proteins to acquire two forms of iron (i.e. heme and ferric ion) in the entire lifecycle of entomopathogenic fungi but also help to better understand the mechanisms of fungus–host and inter–fungus interactions.

Molecular cloning, characterization and expression analysis of two 12-oxophytodienoate reductases (NtOPR1 and NtOPR2) from Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Dylan O’Neill Rothenberg; Muhammad Imran; Sajid Fiaz; Naveed ur Rehman; Sikandar Amanullah; Afifa Younas; Yan Ding; Xianjie Cai; Xiaolong Chen; Lei Yu; et al. (Molecular Biology Reports, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Depression Augments Plasma APOA4 without Changes of Plasma Lipids and Glucose in Female Adolescents Carrying G Allele of APOA4 rs5104 - Qi Wei Guo; Yan Jun Si; Yi Lin Shen; Xu Chen; Mei Yang; Ding Zhi Fang; Jia Lin (Journal of Molecular Neuroscience, 2021)

Cardiac Adipose Tissue Contributes to Cardiac Repair: a Review - Yan Lin; Siyin Ding; Yuwen Chen; Meixiang Xiang; Yao Xie (Stem Cell Reviews and Reports, 2021)

Mid-Level Riverine Outflow Matters: A Case of Microplastic Transport in the Jiulong River, China - Yifan Li; Siguang Liu; Mengyang Liu; Wei Huang; Kai Chen; Yongcheng Ding; Fangzhu Wu; Hongwei Ke; Linghao Lou; Yan Lin; Mingyu Zhang; Fengjiao Liu; et al. (Frontiers in Marine Science, 2021)
Riverine outflow is one of the major pathways for microplastic transportation to coastal environments. Research on the output of microplastics in small- or medium-sized rivers will help accurately understand the status of their marine loads. In this study, we used both trawling and pumping methods to collect microplastics of different sizes in the Jiulong River Estuary and Xiamen Bay. We found that the abundance of small microplastics (44 μm–5.0 mm) was at least 20 times higher than the large particles (0.33–5.0 mm). The abundance of the large particles ranges from 4.96 to 16.3 particles/m 3 , and that of the small particles ranged from 82.8 to 918 particles/m 3 . Granule was the dominant shape (>60%), and polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) were the most common components. The riverine flux of small microplastics (44 μm–5 mm, 472 ± 230 t/y) was at a medium level and was eight times greater than that of large particles (0.33–5.0 mm, 61.2 ± 2.6 t/y). The behavior of the large microplastics was relatively conservative, whose abundance had a significant correlation with salinity ( R 2 = 0.927) and was mainly influenced by physical factors. In contrast, results of statistical analysis revealed that more complicated factors influenced the small microplastics.

Plant-derived antioxidants incorporated into active packaging intended for vegetables and fatty animal products: a review - Yan Zhang; Baoying Wang; Fangfang Lu; Lin Wang; Yanhong Ding; Xinya Kang (Food Additives & Contaminants: Part A, 2021)

New insights into the fine-scale history of western–eastern admixture of the northwestern Chinese population in the Hexi Corridor via genome-wide genetic legacy - Hongbin Yao; Mengge Wang; Xing Zou; Yingxiang Li; Xiaomin Yang; Ailin Li; Hui-Yuan Yeh; Peixin Wang; Zheng Wang; Jingya Bai; Jianxin Guo; Jinwen Chen; et al. (Molecular Genetics and Genomics, 2021)

Two new 8-isopentenyl isoflavane derivatives from Astragalus dolichochaete diels - Ding-Wei Wang; Chao-Jiang Xiao; Lin Qiu; Xin-Yan Tian; Xiang Dong; Bei Jiang (Natural Product Research, 2021)

Differences in Soil Microbial Community Composition Between Suppressive and Root Rot-Conducive in Tobacco Fields - Yaru Ding; Yulan Chen; Zhengquan Lin; Yangyang Tuo; Hongli Li; Yan Wang (Current Microbiology, 2021)

Sex-specific effects of cigarette smoking on caudate and amygdala volume and resting-state functional connectivity - Fuchun Lin; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Yan Zhou; Hao Lei (Brain Imaging and Behavior, 2021)

Effects of Single-Dose and Long-Term Ketamine Administration on Tau Phosphorylation–Related Enzymes GSK-3β, CDK5, PP2A, and PP2B in the Mouse Hippocampus - Yanning Li; Gehua Wen; Runtao Ding; Xinghua Ren; Chenchen Jing; Lin Liu; Jun Yao; Guohua Zhang; Yan Lu; Baoman Li; Xu Wu (Journal of Molecular Neuroscience, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Molecular characterization of the Krüppel-homolog 1 and its role in ovarian development in Sogatella furcifera (Hemiptera: Delphacidae) - Kui Hu; Ping Tian; Lu Yang; Yan Tang; Lin Qiu; Hualiang He; Wenbing Ding; Youzhi Li (Molecular Biology Reports, 2020)

Mbp1, a component of the MluI cell cycle box‐binding complex, contributes to morphological transition and virulence in the filamentous entomopathogenic fungus Beauveria bassiana - Jin‐Li Ding; Hai‐Yan Lin; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2020)
Summary The Mbp1 protein functions as a DNA‐binding protein in the MluI cell cycle box‐binding complex and plays significant roles in yeast development. In this study, an ortholog of yeast Mbp1, BbMbp1, was characterized in a filamentous insect mycopathogen, Beauveria bassiana . BbMbp1 plays an important role in morphological changes under aerial and liquid environments. On the aerial surface, BbMbp1 was indispensable for the biogenesis of conidiophores and conidiation. Under submerged conditions, the ∆ BbMbp1 mutant displayed abnormal spore‐producing structures, with a dramatic decrease in blastospore yield (~95%). The virulence of the ∆ BbMbp1 mutant was notably weakened, which might be due to the defect in in vivo blastospore formation in the insect. Moreover, disruption of BbMbp1 resulted in a substantial reduction in hyphal growth on cadavers. Comparative transcriptomics revealed that BbMbp1 mediated different transcriptomes during the formation processes of conidia and blastospores. Yeast one‐hybrid assays demonstrated that BbMbp1 was required for transcriptional control of a cell wall protein gene, BbCwp , and an integral membrane protein gene, BbImp that played significant roles in conidiation and blastospore formation respectively. Our results demonstrate that BbMbp1 contributes to the morphological transitions in the pathogenic and saprophytic growth of B . bassiana via different genetic pathways.

Multicenter-Based Population Pharmacokinetic Analysis of Ciclosporin in Hematopoietic Stem Cell Transplantation Patients - Ling Xue; Wen-juan Zhang; Ji-xin Tian; Lin-na Liu; Hai-hong Yan; Wen-wen Zhang; Xiao-liang Ding; Jing-jing Zhang; Li-yan Miao (Pharmaceutical Research, 2020)

Deriving water quality criteria for China for the organophosphorus pesticides dichlorvos and malathion - Ting-ting Ding; Ya-hui Zhang; Yan Zhu; Shi-lin Du; Jin Zhang; Ying Cao; Yi-zhe Wang; Gong-ting Wang; Lian-sheng He (Environmental Science and Pollution Research, 2019)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Sex differences in resting-state cerebral activity alterations in internet gaming disorder - Yawen Sun; Yao Wang; Xu Han; Wenqing Jiang; Weina Ding; Mengqiu Cao; Yasong Du; Fuchun Lin; Jianrong Xu; Yan Zhou (Brain Imaging and Behavior, 2019)

Spatial Distribution of Organophosphorus and Brominated Flame Retardants in Surface Water, Sediment, Groundwater, and Wild Fish in Chengdu, China - Lin Hou; Jingyan Jiang; Zhiwei Gan; YuanYuan Dai; Ping Yang; Yan Yan; Sanglan Ding; Shijun Su; Xiaoming Bao (Archives of Environmental Contamination and Toxicology, 2019)

Design, synthesis, bioactivity, and DFT calculation of 2-thiazolyl-hydrazone derivatives as influenza neuraminidase inhibitors - Man-Ying Cui; Jian-Xia Nie; Zhong-Zhong Yan; Meng-Wu Xiao; Ding Lin; Jiao Ye; Ai-Xi Hu (Medicinal Chemistry Research, 2019)

Biotransformation of 20( R )-panaxatriol by the fungus Aspergillus flavus Link AS 3.3950 - Jian Lin Li; Peiyu Ding; Baocheng Jiang; Min Yang; Jie Ren; Yan Song; Guangtong Chen (Natural Product Research, 2019)

Over-expression of the red plant gene R1 enhances anthocyanin production and resistance to bollworm and spider mite in cotton - Xin Li; Xufen Ouyang; Zhengsheng Zhang; Lin He; Yi Wang; Yaohua Li; Jia Zhao; Zhong Chen; Chuannan Wang; Lingli Ding; Yan Pei; Yuehua Xiao (Molecular Genetics and Genomics, 2019)

Posttraumatic Stress Disorder Augments Plasma Triglycerides in TT Homozygotes of rs495225 at Growth Hormone Secretagogue Receptor Gene - Mi Su; Yan Jun Si; Qi Wei Guo; Mei Yang; Xu Chen; Jia Lin; Ding Zhi Fang (Biochemical Genetics, 2019)

The fecal virome of red-crowned cranes - Yan Wang; Shixing Yang; Dawei Liu; Chenglin Zhou; Wang Li; Yuan Lin; Xiaochun Wang; Quan Shen; Hua Wang; Chuang Li; Minghui Zong; Yuzhu Ding; et al. (Archives of Virology, 2019)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

The complete mitochondrial genome of Shigaste humped cattle (Bos taurus) - Xian Guo; Jie Pei; Lin Xiong; Pengjia Bao; Yanbin Zhu; Basang Wangdui; Xiaoyun Wu; Min Chu; Ping Yan; Xuezhi Ding (Conservation Genetics Resources, 2018)

The complete mitochondrial genome of Zhangmu cattle (Bos taurus) - Xian Guo; Pengjia Bao; Lin Xiong; Yanbin Zhu; Basang Wangdui; Xiaoyun Wu; Xuezhi Ding; Jie Pei; Ping Yan (Conservation Genetics Resources, 2018)

Complete mitochondrial genome of Anxi cattle (Bos taurus) - Xian Guo; Xuezhi Ding; Xiaoyun Wu; Pengjia Bao; Lin Xiong; Ping Yan; Jie Pei (Conservation Genetics Resources, 2018)

Sucrose is involved in the regulation of iron deficiency responses in rice (Oryza sativa L.) - Peng-Fei Chen; Lin Chen; Zheng-Rong Jiang; Gao-Peng Wang; Shao-Hua Wang; Yan-Feng Ding (Plant Cell Reports, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Ca2+-CaMKKβ pathway is required for adiponectin-induced secretion in rat submandibular gland - Chong Ding; Zhi-Hao Du; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2018)

Dcf1 Triggers Dendritic Spine Formation and Facilitates Memory Acquisition - Qiang Liu; Ruili Feng; Yu Chen; Guanghong Luo; Huang Yan; Ling Chen; Rongfei Lin; Yuqiang Ding; Tieqiao Wen (Molecular Neurobiology, 2018)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Probiotic properties of lactic acid bacteria isolated from traditionally fermented Xinjiang cheese - Ramila Azat; Yan Liu; Wei Li; Abdurihim Kayir; Ding-bo Lin; Wen-wen Zhou; Xiao-dong Zheng (Journal of Zhejiang University-SCIENCE B, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Mechanical Analysis of Static Stress Within Fault-Pillars Based on a Voussoir Beam Structure - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Roadway Stagger Layout for Effective Control of Gob-Side Rock Bursts in the Longwall Mining of a Thick Coal Seam - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Two new dammarane-type glycosides from Phlomis umbrosa - Ming-Ming Ding; Fu-Lin Yan; Jing Tan; Yi-Xiao Bai; Xiang Wang; Yan-Xia Yang (Natural Product Research, 2014)

Continental flood basalts of the Huashan Group, northern margin of the Yangtze block – implications for the breakup of Rodinia - Qi Deng; Jian Wang; Zheng-Jiang Wang; Xuan-Ce Wang; Yan-Sheng Qiu; Qing-Xiong Yang; Qiu-Ding Du; Xiao-Zhuang Cui; Xiao-Lin Zhou (International Geology Review, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Combined action of antioxidant defense system and osmolytes in chilling shock-induced chilling tolerance in Jatropha curcas seedlings - Zhong-Guang Li; Ling-Xuan Yuan; Qiu-Lin Wang; Zhi-Liu Ding; Chun-Yan Dong (Acta Physiologiae Plantarum, 2013)

Infusion of Endothelial Progenitor Cells Accelerates Hematopoietic and Immune Reconstitution, and Ameliorates the Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Chong Chen; Guoliang Song; Zhiling Yan; Shijuan Xu; Lu Jia; Shuang Ding; Jiang Cao; Wei Chen; Hai Cheng; Zhenyu Li; Wei Sang; et al. (Cell Biochemistry and Biophysics, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Synthesis, Crystal Structure, Interaction with BSA and Antibacterial Activity of La(III) and Sm(III) Complexes with Enrofloxacin - Yan-Jun Wang; Rui-Ding Hu; Dong-Hua Jiang; Ping-Hua Zhang; Qiu-Yue Lin; Yun-Yun Wang (Journal of Fluorescence, 2011)

Fast Cleanup System Combined with a Dioxin-responsive Element-driven Luciferase Bioassay for Analysis of Polychlorinated Dibenzo-p-dioxins/furans in Sediments and Soils - How-Ran Chao; Ya-Fen Wang; Ding-Yan Lin; Yi-Ting Cheng; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)

Overexpression of PPARγ can down-regulate Skp2 expression in MDA-MB-231 breast tumor cells - Jie Meng; Yun Ding; Aiguo Shen; Meijuan Yan; Fei He; Huoyan Ji; Lin Zou; Yonghua Liu; You Wang; Xiaowei Lu; Huimin Wang (Molecular and Cellular Biochemistry, 2010)

Preparation of high-affinity rabbit monoclonal antibodies for ciprofloxacin and development of an indirect competitive ELISA for residues in milk - Bin Huang; Yun Yin; Lei Lu; Hai Ding; Lin Wang; Ting Yu; Jia-jin Zhu; Xiao-dong Zheng; Yan-zhen Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

A new dihydroisocoumarin from the rhizomes of Notopterygium forbesii - Yan-Hui Li; Fan Luo; Shu-Lin Peng; Jian Liang; Li-Sheng Ding (Natural Product Research, 2006)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)